Short-term daily teriparatide in patients with rheumatoid arthritis. Issue 3 (4th May 2018) - Kaneko, Tetsuya; Okamura, Koichi; Yonemoto, Yukio; Okura, Chisa; Suto, Takahito; Tachibana, Masahiro; Tamura, Yasuyuki; Inoue, Makoto; Chikuda, Hirotaka
Abstract: Objective: The aim of this study was to compare the efficacy of six-month teriparatide treatment followed by six-month bisphosphonate therapy with 12-month bisphosphonate monotherapy in Japanese rheumatoid arthritis (RA) patients who had not been previously treated for osteoporosis. Methods: A total of 34 RA patients with osteoporosis were enrolled. Thirteen patients received six-month teriparatide prior to six-month minodronate therapy (PTH group), and 21 patients received 12-month minodronate therapy (BP group). Bone mineral density (BMD), and bone turnover markers were measured prior to and 6 and 12 months after the initiation of treatment. Results: Bone mineral density of the spine was significantly increased after 12 months of treatment in both groups. In the PTH group, the mean percent change of BMD of the spine was significantly higher at 12 months after the initiation of treatment, as compared to the BP group (PTH group: 9.9 ± 1.5%, BP group: 5.5 ± 0.7%). Femoral neck BMD was significantly increased only in the PTH group after 12 months. Conclusion: Therapy involving six-month teriparatide followed by six-month minodronate therapy increased spine BMD to a greater degree than 12-month minodronate monotherapy. The strategy of short-term administration of teriparatide for RA patients with osteoporosis might be useful when additional bisphosphonate therapy is considered.